Analysis of the Role of Productive Waqf as a Fiscal Policy Instrument in Islamic Economic - Asep Hasan Sulaeman; Rohman Pranoto; Cahyudi Prima; Tatang Hidayat; Miftah Wangsadanureja (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
This study looks at how productive waqf can be a key tool in fiscal policy under an Islamic economic system, highlighting its ability to help a country achieve financial independence. The study uses a qualitative library research approach to gather and combine information from historical Islamic texts, scientific articles, and official documents about public finance. The results show that productive waqf is an important and lasting source of income for the government, helping it fund public services like education and infrastructure without having to take on debt that involves interest or pay too much in taxes. Historical models from the time of Caliph Umar bin Khattab, handled through the Baitul Maal, show a good example of a balanced budget and fair sharing of wealth. In today's situation, even though Indonesia's yearly cash waqf potential could be as high as Rp 15 trillion to Rp 180 trillion, there is still a big gap in literacy, which is a major problem. Modern innovations such as Cash Waqf-Linked Sukuk, digital platforms, and partnerships with small businesses—like those used by institutions like Al-Azhar—show how productive assets can have a big impact by creating a large multiplied effect. This study says that including waqf in the official financial system is important for reaching falah and the Sustainable Development Goals, but only if there is good management by nadzir, helpful laws, and the use of digital technology.